The Effects of Cannabidiol and Prognostic Role of TRPV2 in Human Endometrial Cancer - Oliviero Marinelli (International Journal of Molecular Sciences, 2020)
Several studies support, both in vitro and in vivo, the anti-cancer effects of cannabidiol (CBD), a transient receptor potential vanilloid 2 (TRPV2) ligand. TRPV2, often dysregulated in tumors, is associated with altered cell proliferation and aggressiveness. Endometrial cancer (EC) is historically divided in type I endometrioid EC and type II non-endometrioid EC, associated with poor prognosis. Treatment options with chemotherapy and combinations with radiation showed only limited efficacy. Since no data are reported concerning TRPV2 expression as well as CBD potential effects in EC, the aim of this study was to evaluate the expression of TRPV2 in biopsies and cell lines as well as the effects of CBD in in vitro models. Overall survival (OS), progression-free survival (PFS), cell viability, migration, and chemo-resistance have been evaluated. Results show that TRPV2 expression increased with the malignancy of the cancer tissue and correlated with shorter PFS (p = 0.0224). Moreover, in vitro TRPV2 over-expression in Ishikawa cell line increased migratory ability and response to cisplatin. CBD reduced cell viability, activating predominantly apoptosis in type I cells and autophagy in mixed type EC cells. The CBD improved chemotherapeutic drugs cytotoxic effects, enhanced by TRPV2 over-expression. Hence, TRPV2 could be considered as a marker for optimizing the therapy and CBD might be a useful therapeutic option as adjuvant therapy.